Mối liên kết của quá tải tính năng hệ thống, thông tin và giao tiếp trong tích hợp chuyển đổi số: ảnh hưởng của xung đột vai trò - Nguyễn Thúy, Vi; Trần Trí, Dũng; Nguyễn Thị Mai, Trang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
The objective of this study is to examine the impact of System Feature Overload (SFO), Information Overload (IO), and Communication Overload (CO) on Role Conflict (RC), thereby influencing employees' Digital Transformation Integration (DTI) behaviors. Based on data collected from a sample of 322 office employees at businesses implementing digital transformation, the study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the hypotheses. The findings indicate that SFO, IO, and CO contribute to an increase in RC. Furthermore, RC negatively affects DTI. To improve employees' ability to integrate digital transformation, organizations should carefully assess actual workload levels and invest appropriately in digital transformation initiatives.
Keywords: Digital transformation integration; Role conflict; Communication overload; Information overload; System feature overload